Research Progress on Leaching of Rare Earth Elements in Phosphogypsum - Jing TAN; Guodong LI; Dahai YOU; Jin ZHANG; Chaohong ZHANG; Xinghua PENG; Li ZHANG; Xiuquan HU (Medžiagotyra)
With the increasing global demand for rare earth elements and the depletion of traditional mineral resources, recycling rare earth elements from industrial solid waste has become an important direction of sustainable resource utilization. Phosphogypsum is a kind of industrial by-product with huge output and trace rare earth elements, its effective treatment and resource utilization are of great significance for environmental protection and economic development. Based on the occurrence state of rare earth elements in phosphogypsum, the research progress of leaching of rare earth elements in phosphogypsum was reviewed in this paper. The leaching mechanism and influencing factors of different leaching agents were summarized and analyzed.